DOI: 10.3990/1.9789036531269
|View full text |Cite
|
Sign up to set email alerts
|

Vibro-accoustical instabilities induced by combustion dynamics in gas turbine combustors

Abstract: Vibrations are unavoidable phenomena in any working machine. Gas turbines are not an exception. Vibrations in a typical combustion chamber of a gas turbine are directly related to pressure changes induced by the flow and fluctuation in heat release by the flame. When thermo-acoustic instabilities are not present in the system, the amplitude of vibration is relatively small and the turbine can work for a desired long In Chapter 4 fluid-structure interaction computations (FSI) between flue gas and liner, with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 47 publications
(69 reference statements)
0
17
0
Order By: Relevance
“…However, earlier performed analyses on different types of noise sources in the combustor chamber showed that the acoustic noise induced by the unsteady combustion process is the strongest acoustic source [19]. The acoustic phenomenon in a gas turbine combustor can originate from different sources.…”
Section: -D(ç)_mentioning
confidence: 99%
“…However, earlier performed analyses on different types of noise sources in the combustor chamber showed that the acoustic noise induced by the unsteady combustion process is the strongest acoustic source [19]. The acoustic phenomenon in a gas turbine combustor can originate from different sources.…”
Section: -D(ç)_mentioning
confidence: 99%
“…Prakash [2] studied the dynamic performances of chamber flame at different gas equivalent ratios, and the interaction between acoustic pressure and flame was analysed. Artur [3] analysed the heat-acoustic instability, and the interaction between temperature field and acoustic pressure field was studied. Huls [4] studied the vibration in combustion chambers basing on acoustic-elastic finite element model and sound vibration test.…”
Section: Introductionmentioning
confidence: 99%
“…If these acoustic oscillations modify the burning rate with the correct phasing, the intensity of the instabilities will be increased, causing amplified flame oscillations. This then causes larger amplitude acoustic disturbances to be produced from the unsteady heat release oscillations, which will drive instability growth [1,2,3].…”
Section: Introductionmentioning
confidence: 99%